Cross-legged sitting posture effect on lumbar proprioception in young adults: a cross-sectional study - Rania N. Karkousha (SpringerOpen, 2021)
Abstract Background The cross-legged sitting posture (CLS) is assumed by young adults’ results in a bent and unbalanced posture. The study purpose was to assess the effect of sitting in a cross-legged position (knee on knee) on lumbar proprioception. Thirty-six participants of both genders aged from 18 to 25 were selected and divided equally into group A who adapt to a cross-legged sitting posture and group B who adapt to erect sitting (not prefer cross-legged sitting). The Biodex System 3 pro isokinetic dynamometer was utilized to assess the lumbar proprioception by testing the lumbar region repositioning accuracy. Results The lumbar repositioning error of group A increased statistically significantly as compared to group B (p < 0.05). Conclusions Cross-legged sitting posture negatively affects lumbar proprioception compared with participants who adapt to erect sitting, and this effect should be considered in the avoidance of sitting in a cross-legged position and in prevention and intervention programs of lumbar proprioception impairment.